Pengaruh leverage, debt maturity, ukuran perusahaan, dan usia perusahaan terhadap kinerja perusahaan - Datun, Fajar Wakhi; Indrati, Menik (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to analyze the effect of Debt to Asset Ratio, Short Term Debt, company size, and company age on company performance. This study uses multiple linear regression analysis in its testing. In this study, there were 32 companies that met the criteria from a total observation of 45 companies with research objects in LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The Debt to Asset Ratio variable has a negative effect on company performance. Short Term Debt variable has a negative effect on company performance. Company size and company age variables have a positive effect on company performance. This research can also be taken into consideration for investors to be more careful in interpreting publications by companies in terms of making decisions with investment decisions, especially so that they can ensure that the investments they make in companies will bring benefits in the future. Companies should analyze aspects that can affect company performance so that they can be improved in order to encourage companies to be better with good company performance.